2016
DOI: 10.5755/j01.itc.45.1.9246
|View full text |Cite
|
Sign up to set email alerts
|

Analysis the Parameters of the Adaptive Controller for Quality Control of Dissolved Oxygen Concentration

Abstract: The wastewater treatment plant can be considered as a dynamic large scale complex system, in which the most important control parameter is the dissolved oxygen concentration in the aerobic zone. The air is supplied to this zone by the aeration system. In the paper, both the sequencing batch reactor and the aeration system are modelled and used as plant of control performed by the cascade nonlinear adaptive control system extended by the anti-windup filter. The effect of certain parameters of the adaptive contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In summary, the aim of this paper is to design the supervisory control system for adaptive phase and work cycle management of SBR, in wide operating range. This paper further develops the research works presented in [4,9,13]. The ASM2d model, presented by International Water Association task group [8], was used to simulate the plant.…”
Section: Problem Statement and Main Contributionmentioning
confidence: 84%
See 2 more Smart Citations
“…In summary, the aim of this paper is to design the supervisory control system for adaptive phase and work cycle management of SBR, in wide operating range. This paper further develops the research works presented in [4,9,13]. The ASM2d model, presented by International Water Association task group [8], was used to simulate the plant.…”
Section: Problem Statement and Main Contributionmentioning
confidence: 84%
“…Broad range of control technologies have been researched and applied to DO control, e.g. adaptive controller [4,9,13], predictive controller [5,7,11,12,18], multivariable PID controller [19], fuzzy controller [3,14], fuzzy predictive controller [15,20]. Extensive review of DO control can be found in [1].…”
Section: Survey Of Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…From the hydrodynamic point of view, the TPF mixtures identification is focused on evaluations of flow patterns, flow resistance and void fraction of the mix- Table 1 Examples of TFP applications in the industry industry / phenomena application description aeration systems sewage aeration biological sewage treatment plants [16,46] aerobic bacteria injection of free oxygen to ensure the bacteria growth [112] bio-and petrochemical processes bubbles columns in physical and chemical processes identification of bubbles to study mass transfer in chemical reactions [30,101], evaluation of air-bubbles plumes existence [2] air-lift columns intensity of the process depends on the bubbles size [5,71,19] control of the gas stream to force the liquid movement [12,20] ejectors flotation processes in the extractive industry [166] sedimentation processes to precipitate some fractions of the liquid [93], chemical reactors electrolysis the intensity of the process identified from the gas phase [109,81], evaluated size of the gas bubbles indicates the process quality heating devices heat exchange gas existence is undesirable and denotes the boiling liquid [139] cavitation rotational pump detection of this phenomena warns of pump's blades erosion or leakage [85,169] ture [34,125,26] . Additionally, to describe the mass transfer it is required to determine other flow parameters like mass transfer coefficient, gas bubbles coalescence and finally the interfacial surface area.…”
Section: Introductionmentioning
confidence: 99%
“…The costs of implementing effective control and optimization algorithms in a WWTP are much lower than its modernization.Previous studies reported various structures and technologies of the DO control system. The cascade nonlinear adaptive control system, extended by the anti-windup filter, was applied [3]. Furthermore, the parameter analysis of the adaptive controller used for quality control was performed.…”
mentioning
confidence: 99%